THE EFFECT OF WORKLOAD AND PROFESSIONAL COMPETENCE ON IMPROVING TEACHER PERFORMANCE WITH THE MERDEKA TEACHING PLATFORM (PMM) AS A MODERATION VARIABLE - Sitti Nurbaya Sulaeman; Suhardi M Anwar; Ilham Tahier; Hadi Pajarianto, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
This study aims to analyze the influence of workload and professional competence on improving teacher performance, with the Independent Teaching Platform (PMM) as a moderation variable. The research method used is quantitative with a survey approach, where data is collected through questionnaires distributed to teachers of Elementary School Group IX, Wara Timur District, Palopo City. Data analysis was carried out using multiple linear regression analysis and Moderated Regression Analysis (MRA) with the help of SmartPLS 3.3 software. The results showed that the teacher's workload did not have a significant influence on improving performance, while professional competence was proven to have a significant influence on improving teacher performance. However, the Merdeka Mengajar (PMM) platform does not moderate the influence of professional competence or workload on performance improvement. These results show that the improvement of teachers' professional competence plays a greater role in improving performance than the workload and that the role of the Merdeka Mengajar (PMM) platform in supporting performance improvement still needs to be optimized.